2016
DOI: 10.2174/1570161113666151030105431
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Risk and Adequacy of Prophylaxis in High Risk Pregnancy in the Arabian Gulf

Abstract: Objectives: To estimate the prevalence of venous thromboembolism (VTE) risk factors in pregnancy and the proportion of pregnancies at risk of VTE that received the recommended prophylaxis according to the American College of Chest Physicians (ACCP) 2012 published guidelines in antenatal clinics in the Arabian Gulf.Methods: The evaluation of venous thromboembolism (EVE)-Risk project was a non-interventional, cross-sectional, multi-centre, multi-national study of all eligible pregnant women (≥17 years) screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…The risk profile analysis of our patients revealed that obesity was the most prevalent risk factor, followed by multiparity. These findings are consistent with those from a large cross-sectional study in which obesity was manifest in 76% of the examined VTE cases, and multiparity was the second most prevalent risk factor observed in 33% of patients [10]. In another case-control study conducted among Sudanese pregnant and postpartum patients with VTE, it was found that family history, followed by multiparity and cesarean section delivery was the most significant risk factors (ORs: 7.4, 2.2, and 2, respectively) [11].…”
Section: Discussionsupporting
confidence: 91%
“…The risk profile analysis of our patients revealed that obesity was the most prevalent risk factor, followed by multiparity. These findings are consistent with those from a large cross-sectional study in which obesity was manifest in 76% of the examined VTE cases, and multiparity was the second most prevalent risk factor observed in 33% of patients [10]. In another case-control study conducted among Sudanese pregnant and postpartum patients with VTE, it was found that family history, followed by multiparity and cesarean section delivery was the most significant risk factors (ORs: 7.4, 2.2, and 2, respectively) [11].…”
Section: Discussionsupporting
confidence: 91%
“…16 However, perceived VTE risk in the present study was higher than that reported in two previous cross-sectional studies. In a noninterventional, multinational study conducted at seven centers in the Arabian Gulf countries, 32% (1,337 of 4,131) of the eligible pregnant women were at VTE risk, 17 almost equal to two-thirds of that observed for the Middle-East in the present study. In another study in Ireland, 40% (145 of 364) of the pregnant and postpartum women were at risk, 18 nearly half of that observed for Eurasia in the present study.…”
Section: Discussionsupporting
confidence: 37%
“…There can be more than one risk factor for VTE in one patient. Obesity and multiple pregnancies were the risk factors for VTE in Middle East population [5]. Peripartum Pulmonary Embolism DOI: http://dx.doi.org/10.5772/intechopen.84688…”
Section: Risk Factorsmentioning
confidence: 99%
“…Peripartum thromboembolism common, as still the prophylaxis, is adequately administered in high-risk patients [5]. Those patients with a higher risk of thromboembolism during pregnancy and peripartum should receive the thromboprophylaxis to prevent proper thromboembolisms (Figure 5).…”
Section: Preventionmentioning
confidence: 99%